Clinical diagnostic of bovine enzootic vesical hematuria by urinalysis in Oxapampa, Peru - Verde Z., Gemma (2017)
The field study was conducted in Oxapampa, Pasco, Peru to clinically diagnose bovine enzootic vesical hematuria (BEVH) by the urinalysis test, in conjunction with clinical and semiological evaluation of the animals, and the assessment of the farm. Urinary samples were collected by external manual stimulation of the perivulvar and perineal area in 211 female cattle, older than 6 months of age, and naturally exposed to consumption of braken fern – Pteridium aquilinum (Pa). Samples were analyzed using reagent strips (RS), physicochemical characteristics (color, turbidity, specific weight and pH), complementary chemical tests (protein, glucose and bilirrubin), and microscopic evaluation of the sediment (EMS). EMS is a confirmatory test for BEVH and highly relevant for subclinical cases (microhematuria). EMS results varied in intensity and therefore, a new classification based on the number of red blood cells per microscopic field was proposed. The relationship between EMS and RS, physicochemical test and complementary chemical tests were evaluated. A 26.1% prevalence of BEHV was found in the area. The statistical analysis showed that age and the interval to the last parturition can be considered as predisposing factors for BEVH.